Safety Assessment of Questionable Food Additives in the Halal Food Certification: A Review - Mariyam, Siti; Bilgic, Huseyin; Rietjens, Ivonne M.C.M.; Susanti, Devi Yuni (UIN Sunan Gunung Djati Bandung, 2022)
Food additive demand was increased due to the higher need for long-lasting and ready-to-eat food. Some food ingredients are concerned about their halal status due to the source of ingredients and technology processes. Halal is not only related to the religious motif but also the food's integrity. This research aims to describe the scientific relevance of some questionable food additives in halal food certification in HFFIA (Halal Feed and Food Inspection Authority). The ingredients of food that have unclear halal status were subjected in this study. Literature reviews from some scientific sources for relevant papers in English were used to understand the suspected food additive. Food safety is included of certification process; it is essential for certificate application and verification procedures requirement. Food additives are used at food industry to enhance food quality. Some food additives have questionable halal status because of their principal ingredients. According to this study, those food additives were found in the screening process. The plant-based ingredients are good alternatives to ensure the halal status of those food additives. Also, the use of raw materials and processing aids from halal-approved origins and suitable processing technologies will provide the halal status and give the trustworthy among consumers. This review may serve as a basis for using food additives considering halal not only for further research but also for food industry.